The Influence of Top Management Team Characteristics on BPD Performance - Tulung, Joy Elly; Ramdani, Dendi (Universitas Prasetiya Mulya, 2015)
Based on ”upper echelons theory”, this paper investigates the relation between top management team composition and BPD performance. For top management team characteristics, we employ age, level of education, background of education, gender, and functional background, while for measured the BPD performance we employ return on asset (ROA), return on equity (ROE), capital adequacy ratio (CAR), net interest margin (NIM), loan to deposit ratio (LDR), non-performing loan (NPL) and operation expenses to operation income (BOPO). The results show that all characteristics have positive significant influences on BPD performance.